Canadians Denied: A Queer Diasporic Analysis of the Canadian Blood Donor - Dryden, OmiSoore (Atlantis, 2010)
Canadian Blood Services (CBS), through its blood donor screening process, constructs a blood donor body/subject that is framed through a series of exclusions. Using queer diasporic analysis, I explore and interrogate not only the construction of the blood donor body/subject, but also the political and legal challenges brought to this construction.